Effect of Chlorhexidine and Green Tea Extract Application on The Microtensile Bond Strength and Durability of Etch-and-Rinse Adhesives. - Mahsa Ahmadi Shadmeri; Alireza Boruziniat; Hossein Chalaki Nia (Mashhad University of Medical Sciences, 2022)
Introduction: Despite improvements in dentin bonding, the bond will be demolished over time and decreased by water and matrix metalloproteinase (MMP). This study aimed to evaluate the effects of the combination of different methods of MMP inhibition and detect the possible synergic effect on strength and bond durability. Methods: Thirty human third molar teeth without any cracks or decay were used in this study. The occlusal surface of teeth were removed, and dentine surfaces were flattened with silicon carbide plates. After preparing for restoration, teeth were divided into 4 groups, including 1- the control group, 2- the chlorhexidine (CHX) 2% group, 3- the green tea (GT) extract 15%+rinse+CHX 2% in 30 sec, and 4- GT extract15%+rinse+CHX 2% in 60 sec for the application time of GT. Composite samples were divided into two groups, and microtensile bond strength was evaluated immediately and 3 months after storage in water. The fracture type of samples was then evaluated using a stereomicroscope. Results: The immediate bond strength had no significant difference in experimental groups. The mean bond strength for GT+CHX in 30 and 60 sec after a 3-month storage had a significant difference with the 3-month storage control group, however, not significant with the immediate control group. Conclusion: The use of GT extract with CHX led to bond durability after a 3-month storage. Further studies are required for investing the in vivo effect of this combination.